Environmental DNA metabarcoding complements bottom trawling and detects fish species beyond recorded ranges in the Chukchi Borderland, Central Arctic Ocean - Hai Li; Fang Yang; Xiang Zhang; Ran Zhang; Rui Wang; Xing Miao; Shigang Liu; Puqing Song; Yuan Li; Longshan Lin (Marine Environmental Research, 2026)

Transcriptome sequencing of the Epinephelus lanceolatus reveals the potential physiological responses of mesopelagic fishes to light stress from deep-sea mining - Xiang Zhang; Tianci Wang; Yuan Li; Puqing Song; Shigang Liu; Yuzhuo Liao; Hai Li; Longshan Lin (Marine Pollution Bulletin, 2026)

Unraveling geographical heterogeneity and spatial distribution of Long pepper fruits: An integrative analytical perspective - Shuwen Geng; Conghui Duan; Ying Ye; Yuye Gao; Yujia Zhai; Fangyuan Gao; Yuewei Ge; Yang Chen; Yunxia Li; Rongping Zhang; Xinglong Chen; Jian-lin Wu; et al. (Food Chemistry, 2026)

Delineating fish ecological corridors in a subtropical bay using eDNA metabarcoding: A case study from Xiamen Bay, China - Hai Li; Fang Yang; Xiang Zhang; Yuzhuo Liao; Yuan Li; Puqing Song; Shigang Liu; Longshan Lin (Regional Studies in Marine Science, 2026)

Microplastics found in Weddell seal placenta in Antarctica, potential threatening marine ecosystem health - Xing Miao; Conghui Peng; Renxin Zhang; Baohong Chen; Zongzheng Chen; Hui Lin; Tingting Fu; Yuan Li; Longshan Lin (Journal of Hazardous Materials, 2026)

A unique demersal fish fauna in the Chukchi Borderland, Central Arctic Ocean - Ran Zhang; Hai Li; Puqing Song; Rui Wang; Jing Zhang; Tianci Wang; Shusen Fu; Shigang Liu; Yuan Li; Xing Miao; Lei Yang; Longshan Lin (Reviews in Fish Biology and Fisheries, 2025)

Screening of predatory fish species for larvae of Acanthaster solaris and quantitative analysis techniques of environmental DNA - Zhanbiao Hu; Shigang Liu; Wei Wang; Zhongjie Wu; Zhaoqun Liu; Kar-Hoe Loh; Yuan Li; Longshan Lin (Journal of Experimental Marine Biology and Ecology, 2025)

The Effect of the Marine Environment on the Distribution of Sthenoteuthis oualaniensis in the East Equatorial Indian Ocean - Shigang Liu; Liyan Zhang; Peng Lian; Jianhua Kang; Puqing Song; Xing Miao; Longshan Lin; Rui Wang; Yuan Li (Fishes, 2025)
Sthenoteuthis oualaniensis is one of the most commercially important marine cephalopod species distributed throughout tropical and subtropical waters of the Indo-Pacific Seas. The Indian Ocean is a main fishing ground for S. oualaniensis with a high population density. To explore the distribution of S. oualaniensis in the east equatorial Indian Ocean, four surveys were carried out using light-lift-net fishing vessels. Meanwhile, marine environmental data were also collected, including the sea surface temperature, sea temperature at 100 m depth, mixed layer depth, sea surface chlorophyll-a concentration, sea surface height, and eddy kinetic energy. Generalized Additive Models were used to analyze the relationship between the catch per unit effort (CPUE) for S. oualaniensis and environmental factors. The results showed that the average CPUE of S. oualaniensis was 14.55 kg/h in the four surveys, which was considerably lower than in the South China Sea and Northwest Indian Ocean. In terms of seasonal distribution, the high-CPUE stations were closer to the continental shelf in spring, while they shifted towards the deeper and offshore water in autumn, demonstrating a seasonal migration trend. Pearson correlation analysis showed that CPUE reflected a significant negative correlation with both sea temperature at 100 m depth and eddy kinetic energy (p

Predicting the potential distribution of major marine mammals in the Cosmonaut Sea - Yufei Dai; Fanyi Meng; Fuxing Wu; Xing Miao; Denghui Yan; Mingding Zhong; Shunan Cao; Yuli Wei; Longshan Lin (Frontiers in Marine Science, 2025)
The Southern Ocean, a critical marine region on Earth, is undergoing significant environmental changes due to global climate change, including reductions in sea ice extent, ocean acidification, and alterations in the Antarctic Circumpolar Current (ACC). The Cosmonaut Sea, notable for its dynamic sea ice and rich biological activity, remains one of the least explored regions in the Southern Ocean, with limited data on its marine mammal populations. This study conducted during the 38th Chinese National Antarctic Research Expedition (CHINARE) from January to March 2022, collected systematic data on marine mammal occurrences. Species distribution modeling (SDM) was used to assess the influence of environmental variables on the distribution of the most abundant marine mammal species observed in the Cosmonaut Sea, including humpback whales ( Megaptera novaeangliae ), crabeater seals ( Lobodon carcinophaga ), and Antarctic minke whales ( Balaenoptera bonaerensis ). Our results indicated significant performance variations among the different algorithms, with ensemble model yielding more accurate predictions. Environmental variables such as water depth, sea surface height, and mixed layer thickness were identified as significant factors influencing habitat suitability for different species. Humpback whales were found to have the widest distribution range, followed by Antarctic minke whales and crabeater seals. Generally, the study provides the first comprehensive analysis of marine mammal distribution in the Cosmonaut Sea, highlighting the effectiveness of ensemble models in ecological predictions. The findings emphasize the importance of integrating high-resolution data and incorporating predator-prey interactions in future studies to improve our understanding and conservation of these complex ecosystems.

Pilot study to reconstruct life history of Diaphus thiollierei from the Arabian Sea by otolith microstructure and microchemistry - Lisheng Wu; Wenxin Zhuang; Qiaohong Liu; Rui Wang; Yuan Li; Longshan Lin; Shufang Liu; Shaoxiong Ding (Acta Oceanologica Sinica, 2024)

Multiple environmental gradients shape the functional structure of macrobenthic communities across the Pacific Arctic shelf - Kun Liu; Yaqin Huang; Weibo Wang; Jianfeng Mou; Junhui Lin; Shuyi Zhang; Longshan Lin; Jun Sun; Zhongyong Gao; Heshan Lin; Xuebao He (Science of The Total Environment, 2024)

Acoustic Target Strength Measurement of Larmichthys crocea Based on the Kirchhoff-Ray Mode Model - Junliang Meng; Yong Tang; Lizhi Sun; Longshan Lin; Yuan Li; Xing Miao; Shigang Liu; Puqing Song (Fishes, 2024)
Larmichthys crocea (L. crocea) is an economically important fish species mainly distributed off the coast of China. In this study, 11 L. crocea samples of different body lengths were collected from aquaculture cages in the East China Sea to measure the acoustic target strength (TS). Using the Kirchhoff-Ray mode (KRM) model, the directional TS of L. crocea was measured at frequencies of 70 kHz, 120 kHz, and 200 kHz. Furthermore, the relationships between TS and body length were determined using the least squares method and the standard b20 equation. The results showed that the TS of L. crocea varied with tilt angle, frequency, and body length. For tilt angles ranging from (−5°, 15°), the equation for fitting TS and body length using the least squares method were TS = 32.99·log10L − 87.36 (70 kHz), TS = 33.26·log10L − 87.77 (120 kHz), and TS = 39.46·log10L − 95.51 (200 kHz). They were expressed in the standard b20 equation as TS = 20·log10L − 71.16 (70 kHz), TS = 20·log10L − 71.23 (120 kHz), and TS = 20·log10L − 71.24 (200 kHz). For tilt angles ranging from (0°, 10°), the equation for fitting TS and body length using the least squares method is TS = 28.69·log10L − 81.71 (70 kHz), TS = 32.30·log10L − 86.44 (120 kHz), and TS = 45.87·log10L − 103.73 (200 kHz). They were expressed in the standard b20 equation as TS = 20·log10L − 70.88 (70 kHz), TS = 20·log10L − 71.10 (120 kHz), and TS = 20·log10L − 71.48 (200 kHz). Moreover, the 18–300 kHz spectral curve showed a decreasing trend in the frequency range from 18 kHz to 30 kHz, while maintaining relatively stable fluctuations in the other frequency ranges. These findings offer a comprehensive understanding of the scattering characteristics of L. crocea and provide a reliable reference of TS for the fishery acoustic assessment of L. crocea.

Analyzing fishery data and exploring the resource status of Antarctic krill based on its environmental dependence - Rui Wang; Shigang Liu; Ran Zhang; Hai Li; Puqing Song; Yuan Li; Longshan Lin (Fisheries Oceanography, 2024)
Antarctic krill Euphausia superba is a key species in the Southern Ocean ecosystem and has important ecological value. It is also one of the main fishery resources in the Southern Ocean with high economic value. In recent years, with the development of krill fishery and rapid climate change, the conservation and management of krill resources have faced unprecedented challenges. The krill resource is different from the general fishery resources. Due to the krill schooling characteristics, fishery data has some advantages over scientific survey data. Reviewing and analyzing the krill fishery data is necessary. Therefore, in this study, four fishery resource indices (FRIs) were calculated based on Antarctic krill fishery data, and based on the environmental dependence of Antarctic krill, the FRI with the strongest environmental dependence was screened by using the Gradient Forest Model, and the step changes of the FRI with strongest environmental dependence was examined by using the sequential t‐test analyses of regime shifts (STARS). The generalized additive model (GAM) to analyze the correlation between the FRI with the strongest environmental dependence and the main environmental factors, and then explore the resource status of Antarctic krill in the study area. The model results showed that the “FRI_hual” had the strongest environmental dependence and was a better indicator of the status of the Antarctic krill in the study area than the others. In the 2009–2010 year, “FRI_hual” had an obvious regime shift. The interaction of environmental factors “ice_area_2” and “SSH_1” has a great impact on “FRI_hual”. Methods used and results obtained in the study can provide new ideas and a scientific reference for future work, including integrated stock assessment of krill and krill resource monitoring, conservation, and management based on the ecosystem.

Pharmacokinetics of nirmatrelvir/ritonavir and the drug-drug interaction with calcineurin inhibitor in renal transplant recipients - Xueyin Xu; Huanxi Zhang; Longshan Liu; Qian Fu; Chenglin Wu; Xiaobin Lin; Kejing Tang; Changxi Wang; Pan Chen (European Journal of Clinical Pharmacology, 2024)

The effect of climate oscillations on skipjack tuna (Katsuwonus pelamis) in the Indian Ocean - Shigang Liu; Liyan Zhang; Rui Wang; Puqing Song; Xing Miao; Hai Li; Yuan Li; Longshan Lin (Journal of Marine Systems, 2024)

First pelagic fish biodiversity assessment of Cosmonaut Sea based on environmental DNA - Yuzhuo Liao; Xing Miao; Rui Wang; Ran Zhang; Hai Li; Longshan Lin (Marine Environmental Research, 2023)

Early life history traits of chub mackerel Scomber japonicus in the Oyashio water revealed by otolith microstructure - Xiaolu Li; Chi Zhang; Yongjun Tian; Longshan Lin; Shigang Liu (Journal of Oceanology and Limnology, 2023)

Identification and DNA Barcoding of Stargazers (Uranoscopidae) From China Seas with a New Finding — Uranoscopus sp. - Zhengsen Yu; Xiaoqi Zeng; Yuan Li; Longshan Lin; Wentao Li; Tianxiang Gao (Thalassas: An International Journal of Marine Sciences, 2023)

Differences in the diversity and community structure of the intestinal microbiota of commercial fishes in the central and southern East China Sea in spring and autumn - Jiali Xiang; Shigang Liu; Puqing Song; Ran Zhang; Yuan Li; Longshan Lin (Environmental Biology of Fishes, 2023)

Effects of Vertical Water Column Temperature on Distribution of Juvenile Tuna Species in the South China Sea - Shigang Liu; Yuan Li; Rui Wang; Xing Miao; Ran Zhang; Siyuan Chen; Puqing Song; Longshan Lin (Fishes, 2023)
In this study, we conducted two surveys in the central and southern parts of the South China Sea, in autumn 2012 and spring 2013. Six juvenile tuna species were caught in each survey. Gradient forest analysis (GFA) and a generalized additive model (GAM) were used to analyze the relationship between the catch per unit effort (CPUE) for the juvenile tuna species and six sea temperature indices for the South China Sea. In the GFA, the temperature difference between the sea surface and 50 m depth (D50) showed the highest importance to CPUE than other indices, which indicates that D50 was the best predictor of the abundance of juvenile tuna species. The GAM analysis showed that lower deep-water temperature, a shallow mixed layer depth, and a higher difference in temperature between the surface and deeper water were associated with increased CPUE. The results indicate that a relatively rapid decrease in vertical water temperature is favorable for the aggregation of juvenile tuna. These results contribute to understanding of the distribution mechanism of juvenile tuna species in the South China Sea and provide a scientific basis for the rational development and utilization of tuna resources.

Genetic diversity monitoring of Chiloscyllium plagiosum from coastal Xiamen between generations - Liyan Zhang; Shigang Liu; Zizi Cai; Jiali Xiang; Puqing Song; Yueping Zhang; Yuan Li; Longshan Lin (Regional Studies in Marine Science, 2023)

Increase of a hypoxia-tolerant fish, Harpadon nehereus (Synodontidae), as a result of ocean deoxygenation off southwestern China - Bin Kang; Andrew Bakun; Longshan Lin; Daniel Pauly (Environmental Biology of Fishes, 2022)

DNA barcoding provides insights into Fish Diversity and Molecular Taxonomy of the Amundsen Sea - Shuai Cao; Yuan Li; Xing Miao; Ran Zhang; Longshan Lin; Hai Li (Conservation Genetics Resources, 2022)

Differentiation and Temperature Adaptation of Pampus Echinogaster Based on Genome-Wide SNPs - Yuan Li; Fangrui Lou; Shigang Liu; Hai Li; Jiali Xiang; Binbin Shan; Longshan Lin; Xuan Zhuang (Frontiers in Marine Science, 2022)
Climate change and overfishing have led to the degradation of the quality and stock of Pampus echinogaster. Exploring the genetic structure and local adaptive evolutionary mechanisms of P. echinogaster is crucial for the management of this species. This population genomic study of nine geographical populations of P. echinogaster in China was conducted by specific-locus amplified fragment sequencing (SLAF-seq). A total of 935,215 SLAF tags were obtained, and the average sequencing depth of the SLAF tags was 20.80×. After filtering, a total of 46,187 high-consistency genome-wide single nucleotide polymorphisms (SNPs) were detected. Based on all SNPs, the population size of the nine P. echinogaster geographical populations was large. The Shantou population had the lowest genetic diversity, and the Tianjin population had the highest. Moreover, the population genetic structure based on all SNPs revealed significant gene exchange and no significant genetic differentiation among the nine P. echinogaster geographical populations, probably because of the population expansion after the last glacial period, the lack of balance between migration and genetic drift, and the long-distance diffusion of eggs and larvae. We suspect that variation of material metabolism, ion transfer, breeding, stress response, and inflammatory reactions-related genes were critical for adaptation to spatially heterogeneous temperature selection in natural P. echinogaster populations.

Estimating the Impact of a Seasonal Fishing Moratorium on the East China Sea Ecosystem From 1997 to 2018 - Lingyan Xu; Puqing Song; Yuyu Wang; Bin Xie; Lingfeng Huang; Yuan Li; Xinqing Zheng; Longshan Lin (Frontiers in Marine Science, 2022)
Fisheries management policies (FMPs) have been implemented in coastal countries to ensure a sustainable supply of seafood and the recovery of species diversity. Because of the depletion of fishery stocks, China has introduced a series of FMPs since 1995, including a seasonal fishing moratorium (SFM), a zero-growth strategy, and a minimum mesh size for fishing nets. Here, we built two mass balance models for 1997–2000 (M1997) and 2018–2019 (M2018) using Ecopath with Ecosim 6.6 to illustrate the interannual changes over the past two decades in the East China Sea (ECS). We then simulated two dynamic scenarios from 1997 to 2018, SFM (M2018 SFM ) and no SFM (M2018 no-SFM ), to test the role of the SFM under fishing pressure in the ECS. Ecopath showed that the ECS ecosystem is becoming more mature, although it is still unstable, featuring lower total primary production/total respiration, longer cycles, faster organic material circulation speed, and a higher omnivorous degree. This suggests a slow recovery for the ECS ecosystem in the past two decades. The biomass of fish in the ECS—especially the planktivores, dominated by small-sized Benthosema pterotum —significantly increased in M2018 versus M1997, but there were fewer medium- and large-sized fish. The keystone species switched from the planktivores/piscivores dominated by Decapterus maruadsi in M1997 to planktivores in M2018. Ecosim illustrated that the SFM has positive effects on fishery resources recovery, especially for commercial fishes (i.e., large yellow croakers and hairtails), as reflected by the significantly higher predicted biomass of fish in M2018 SFM compared to M2018 no-SFM and M1997, although the bioaccumulation was consumed by the intense fishing pressure after the SFM. However, the M2018 SFM prediction for nektons was still lower than the actual value, especially for planktivores, which display a sharp increase in biomass. This should be partly attributable to the policy of the minimum mesh size (<5 cm was banned), which benefits B. pterotum due to its 3.5 cm maximum body size. Therefore, a series of FMPs, rather than only the SFM, functioned together in the ECS ecosystem. However, the mixed trophic impact indicated a negative impact if the fisheries were further developed. Fishery management in the ECS needs to be strengthened by extending the SFM and reducing fishing pressure after the SFM.

Glacier lanternfish (Benthosema glaciale) first found on the continental slope of the Pacific Arctic - Ran Zhang; Yuan Li; Qiaohong Liu; Puqing Song; Hai Li; Rui Wang; Shaoxiong Ding; Longshan Lin (Polar Biology, 2022)

Demersal fish diversity and molecular taxonomy in the Bering Sea and Chukchi Sea - Hai Li; Fang Yang; Xuehua Wang; Yuan Li; Nan Zhang; Ran Zhang; Cheng Liu; Hushun Zhang; Longshan Lin; Puqing Song (Conservation Genetics Resources, 2022)

Potential anticancer activity analysis of piscidin 5-like from Larimichthys crocea - Libing Zheng; Jiayin Qiu; Huihui Liu; Changfeng Chi; Longshan Lin (Acta Oceanologica Sinica, 2022)

Spatio-temporal characteristics of demersal fish community in the Chukchi and northern Bering Seas: significant distributional records and interannual variations in species composition and biodiversity - Ran Zhang; Puqing Song; Hai Li; Rui Wang; Yuan Li; Xing Miao; Longshan Lin; Shaoxiong Ding (Polar Biology, 2022)

Otolith Microstructure Analysis Reveals Different Growth Histories of Japanese Sardine (Sardinops melanostictus) in the Oyashio Waters - Chunlin Liu; Chi Zhang; Yongjun Tian; Liangming Wang; Longshan Lin; Yuan Li; Yoshiro Watanabe (Journal of Ocean University of China, 2022)

An Integrated, Size-Structured Stock Assessment of Antarctic Krill, Euphausia superba - Rui Wang; Puqing Song; Yuan Li; Longshan Lin (Frontiers in Marine Science, 2021)
The Antarctic krill ( Euphausia superba ) fishery is the largest fishery in the Southern Ocean, and it has been operating for over 45 years. In the past decade, the spatial distribution of the krill fishery has focused on the Bransfield Strait off the Antarctic Peninsula (subarea 48.1). However, the high fishing effort and climate change have placed great pressure on krill resources in this region, and conservation concerns have been raised. Because aging krill is difficult and uncertain, we developed an integrated size-structured model to estimate the fishing mortality, recruitment and spawning biomass of krill. The results indicated that in 1992–2011, the average spawning biomass of krill ranged from 1.14 × 10 6 to 1.45 × 10 6 tons, the estimated biomass of the maximum sustainable yield (BMSY) ranged from 3.96 × 10 5 to 4.90 × 10 5 tons and the estimated average recruitment ranged from 2.3 × 10 12 to 5.03 × 10 12 individuals in the research area. We explored the effect of different data weighting schemes for the length data on the assessment output. However, our estimates also have uncertainties. In addition, an attempt was made to analyze the correlation between model-estimated recruitment and mature biomass with climate change. Future stock assessments of krill resources should be comprehensive and multimethod, and the management of krill resources should be based on science that considers the demand of fishing communities and ecosystem protection.

Redistribution of the lizardfish Harpadon nehereus in coastal waters of China due to climate change - Linlong Wang; Zhixin Zhang; Longshan Lin; Xin Peng; Li Lin; Bin Kang (Hydrobiologia, 2021)

Characteristics of Ichthyoplankton Communities and Their Relationship With Environmental Factors Above the Ninety East Ridge, Eastern Indian Ocean - Liyan Zhang; Jing Zhang; Shigang Liu; Rui Wang; Jiali Xiang; Xing Miao; Ran Zhang; Puqing Song; Longshan Lin (Frontiers in Marine Science, 2021)
The Ninety East Ridge is a submarine north–south oriented volcanic ridge in the eastern Indian Ocean. Surface-layer ichthyoplankton collected in this area from September to October were identified by combined morphological and molecular (DNA barcoding) techniques, and their species composition, diversity, and abundance, and correlations with environmental variables were described. Collections comprised 109 larvae and 507 eggs, which were identified to 37 taxa in 7 orders, 20 families, and 27 genera, and were dominated by the order Perciformes and species Vinciguerria sp., Oxyporhamphus micropterus , and Decapterus macarellus . Species abundances at each station and of each species were relatively low, suggesting that this area or the time of sampling were not of major importance for fish spawning. Waters above Ninety East Ridge had lower species diversity but higher species richness than waters further offshore. A generalized additive model revealed that high abundance of ichthyoplanktonic taxa occurred in areas with low sea surface height and high sea surface salinity, temperature, and chlorophyll a concentration. Of these, sea surface height was most correlated with ichthyoplankton abundance. We provided baseline data on surface-dwelling ichthyoplankton communities in this area to aid in development of pelagic fishery resources in waters around the Ninety East Ridge.

Climate change impacts on China’s marine ecosystems - Bin Kang; Gretta T. Pecl; Longshan Lin; Peng Sun; Peidong Zhang; Yuan Li; Linlin Zhao; Xin Peng; Yunrong Yan; Chunyan Shen; Wentao Niu (Reviews in Fish Biology and Fisheries, 2021)

Levels and patterns of genetic variation in Pampus minor: Assessment of a mitochondrial DNA control region sequence - Yuan Li; Liyan Zhang; Jing Zhang; Cheng Liu; Longshan Lin (Acta Oceanologica Sinica, 2021)

Antibacterial and antiparasitic activities analysis of a hepcidin-like antimicrobial peptide from Larimichthys crocea - Libing Zheng; Yuan Li; Jun Wang; Ying Pan; Jia Chen; Weiqiang Zheng; Longshan Lin (Acta Oceanologica Sinica, 2020)

Population genetic structure of Thryssa kammalensis in the Chinese Seas inferred from control region sequences - Jing Zhang; Nan Zhang; Yuan Li; Jiaguang Xiao; Ran Zhang; Tianxiang Gao; Longshan Lin (Marine Biodiversity, 2019)

Species identification and cryptic diversity in Pampus species as inferred from morphological and molecular characteristics - Yuan Li; Yongdong Zhou; Pengfei Li; Tianxiang Gao; Longshan Lin (Marine Biodiversity, 2019)

Primary Productivity Dynamics in the Summer Arctic Ocean Confirms Broad Regulation of the Electron Requirement for Carbon Fixation by Light-Phytoplankton Community Interaction - Yuanli Zhu; David J. Suggett; Chenggang Liu; Jianfeng He; Longshan Lin; Fengfeng Le; Joji Ishizaka; Joaquim Goes; Qiang Hao (Frontiers in Marine Science, 2019)

Fish diversity and molecular taxonomy in the Prydz Bay during the 29th CHINARE - Yuan Li; Liyan Zhang; Puqing Song; Ran Zhang; Liangming Wang; Longshan Lin (Acta Oceanologica Sinica, 2018)

Morphological characteristics and DNA barcoding of Pampus echinogaster (Basilewsky, 1855) - Yuan Li; Yan Zhang; Tianxiang Gao; Zhiqiang Han; Longshan Lin; Xiumei Zhang (Acta Oceanologica Sinica, 2017)

Chinese seventh Arctic scientific expedition - Na Liu; Bin Kong; Lina Lin; Yan He; Yanguang Liu; Longshan Lin; Tao Zhang; Jianfang Chen (Acta Oceanologica Sinica, 2017)

Spatial structure and seasonal changes of nekton assemblages in the Taiwan Strait - Puqing Song; Longshan Lin; Yuan Li; Zhihui Zhong (Acta Oceanologica Sinica, 2016)

Composition of fish species in the Bering and Chukchi Seas and their responses to changes in the ecological environment - Longshan Lin; Yongjun Chen; Yunchih Liao; Jing Zhang; Puqing Song; Xingguang Yu; Risheng Wu; Kwang-tsao Shao (Acta Oceanologica Sinica, 2014)

Toxicity Testing of Waterborne Mercury with Red Sea Bream (Pagrus major) Embryos and Larvae - Wei Huang; Liang Cao; Xiujuan Shan; Longshan Lin; Shuozeng Dou (Bulletin of Environmental Contamination and Toxicology, 2011)